2011
DOI: 10.3109/09638237.2011.608743
|View full text |Cite
|
Sign up to set email alerts
|

Good friends are hard to find? The social networks of people with mental illness 12 years after deinstitutionalisation

Abstract: Appropriate activities and social contexts are still needed to facilitate the social networks of people with mental illness, in particular, for those aged under 65 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 33 publications
4
21
0
1
Order By: Relevance
“…However, a study on people who had been in a mental institution found a larger social network size of 23. 82 Our data also suggest it was the type of relationship (close relationships) rather than the number which was most important for resource exchange and this was supported by other work. 221 …”
Section: Data Limitationssupporting
confidence: 85%
See 1 more Smart Citation
“…However, a study on people who had been in a mental institution found a larger social network size of 23. 82 Our data also suggest it was the type of relationship (close relationships) rather than the number which was most important for resource exchange and this was supported by other work. 221 …”
Section: Data Limitationssupporting
confidence: 85%
“…This finding has been replicated in studies which had also reported a lack of social support, and unmet needs around social interaction and community belonging. 82,83 Studies which examined composition of social networks of individuals with psychosis had found them to contain fewer friends 46 and more service practitioners 84 than the general population, and the onset of psychosis can involve changes in social networks and the loss of friends. 85 It is the multifaceted and dynamic nature of social networks that this study explores, looking beneath a map of connections to understand the negotiated meaning, sets of choices, capacity for growth and qualities such as reciprocity.…”
Section: The Recovery Approachmentioning
confidence: 99%
“…This finding is in line with Norman et al's [1] study and is also consistent with Winefield and colleagues' [31] original data which showed that higher satisfaction with supportive relationships was inversely related to depression. It is likely that many people with psychosis do in fact have social support in place [39], but this may not be beneficial for their mental-health if the social support is seen as poor and inadequate.…”
Section: Perceived Social Supportmentioning
confidence: 99%
“…Many people using mental health services do not access the normal experiences of citizenship. For example, impoverished social networks remain the norm (Forrester-Jones et al 2012). One solution is the development of peer support worker services in health services.…”
Section: 'Hope Is Necessary For Recovery'mentioning
confidence: 99%